Evaluation of Colostral Immunity Against Equine Herpesvirus Type 1 (EHV-1) in Martina Franca's Foals - Di Francesco, Cristina E.; Smoglica, Camilla; De Amicis, Ippolito; Cafini, Federica; Carluccio, Augusto; Contri, Alberto (Frontiers in Veterinary Science, 2020)
Eight Martina Franca pregnant jannies were selected in order to evaluate the transfer of colostral antibodies against Equine Herpesvirus type 1 in their relative foals after immunization with a commercial inactivated vaccine, compared with an unvaccinated group. Samples of serum and colostrums/milk were collected from jannies and foals under study starting from 10 minutes before and up to 21 days after the foaling. Specific anti-EHV-1 antibody titers were evaluated by means a serum neutralization test and the results obtained from both groups were analyzed. The serological titers in the vaccinated jennies was significantly higher (p<0.01). No significant differences were found in the individual time intervals in both groups examined (p>0.05). The antibody titers in milk at the time of delivery and subsequent withdrawal (T0 and T1) were very high in both groups but no significant differences were found between the two groups (p>0.05). In the foal sera, a significant difference was found between foals in the vaccinated group compared with those in unvaccinated group (p < 0.05). Finally, a significant correlation (p < 0.05) was observed between the antibody titers found in serum and colostrum of jennies and the foal titers in the first time-points sampling (up to 12 hours after foaling). The results confirm a substantial homology in the antibody production compared with other most investigated equids, highlighting the efficacy of the vaccination against EHV-1 of the jennies to ensure the protective immunity to their foals during the first weeks after delivery.